Peripherally inserted central catheter causing life‐threatening cardiac tamponade. Issue 2 (3rd November 2014) - Ridler, Simon; Nixon, Chris
Summary: We report a 60‐yr‐old female who had a peripherally inserted central catheter (PICC) for parenteral nutrition (TPN). Insertion was uneventful although the line was seen to extend into the right ventricle. The line was re‐positioned but soon after commencing TPN she collapsed. Computerised tomography pulmonary angiography (CTPA) demonstrated a pericardial effusion with a high fat content. Pericardiocentesis revealed fluid with a high triglyceride content and confirmed pericardial placement of ther tip of the catheter. The patient subsequently made an uneventful recovery. We could only find one other case in the literature of pericardial tamponade after PICC placement in an adult. The exact anatomical course of this line remains unclear despite careful review of radiological imaging. We discuss methods to gauge appropriate line length, possible signs on chest radiography and the immediate management of pericardial tamponade. Resuscitation via a malpositioned line may prove catastrophic; if doubt exsists the line should not be used.